Морфологическая характеристика плацент при переношенной беременности - Траль, Татьяна Георгиевна; Толибова, Гулрухсор Хайбуллоевна; Серегина, Дарья Сергеевна; Кузьминых, Татьяна Ульяновна; Беспалова, Олеся Николаевна (Медицина: теория и практика, 2020)